Facile synthesis methodology and characterization studies of silica‐decorated hybridized anisotropic nanotubes and nanosheets. (23rd September 2022) - Swain, Suchhanda S.; Unnikrishnan, Lakshmi; Mohanty, Smita; Nayak, Sanjay K.
Abstract : Carbonaceous nanomaterials and their derivatives have been inspired tremendous enthusiasm in the scientific community. They have been excogitated as the encouraging attributes and the qualified dispersed phase to develop multi‐functional composites. Particularly, graphene and carbon nanotube (anisotropic fillers) have gained substantial research interest owing to their promising characteristics. This highlights an innovative technique to synthesize hybridized nanotube and nanosheet. Initially, parent materials have been synthesized: The pristine CNT has been modified by acid mixture solution, and reduced graphene oxide has been prepared by chemical reduction method. Henceforth, the self‐assembly in situ sol–gel technique has been endorsed here. The synthesized nanohybrids have been characterized by different spectroscopic techniques: FTIR, Raman, UV, and XPS to confirm the attachment of multifunctionalities; meanwhile, the composition and stability have been investigated from XRD and TGA plots. The magnitude of surface charge and particle size distribution have been evaluated for the parent and hybridized products; further, morphology of all the samples has been authenticated from FESEM and TEM.